2017
DOI: 10.1016/j.athoracsur.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Lung Function Monitoring for Anatomic Lung Resections

Abstract: Daily bedside spirometry might be a helpful diagnostic adjunct for early recognition, and hence, timely treatment, of pulmonary infection after open anatomic lung resections. In addition, minimally invasive techniques not only resulted in a lower rate of pulmonary infections but also resulted in faster postoperative recovery of pulmonary function and shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Postoperative respiratory impairment may be caused by various factors, including surgical factors (site of incision, postoperative pain, and type of surgical procedure), anesthetic factors (residual anesthetics, injurious mechanical ventilation, and type of anesthesia), and many other patient factors (aging and smoking history) [ 67 ]. The operative type has been considered as an important factor that affects post-surgical pulmonary function, particularly when the extent of parenchymal reduction is significant, such as after segmentectomy or lobectomy in VATS [ 68 ].…”
Section: Sapb and Lung Function Recoverymentioning
confidence: 99%
“…Postoperative respiratory impairment may be caused by various factors, including surgical factors (site of incision, postoperative pain, and type of surgical procedure), anesthetic factors (residual anesthetics, injurious mechanical ventilation, and type of anesthesia), and many other patient factors (aging and smoking history) [ 67 ]. The operative type has been considered as an important factor that affects post-surgical pulmonary function, particularly when the extent of parenchymal reduction is significant, such as after segmentectomy or lobectomy in VATS [ 68 ].…”
Section: Sapb and Lung Function Recoverymentioning
confidence: 99%
“…The postoperative recovery of forced expiratory volume in 1 second has been shown to be faster in patients who undergo minimally invasive anatomic lung resection compared with OT. 37 The benefit of the VATS approach seems to disappear after 3 months, and, at that point, loss of pulmonary function is equivalent for VATS and OT. 38 Second, our study was conducted using the French administrative database, which includes all centers performing LC surgery in France whatever the type and the volume of activity.…”
Section: Postoperative Mortalitymentioning
confidence: 98%
“…Pulmonary function testing during hospitalization is conducive to the early detection of pulmonary infections. Gregor et al performed postoperative pulmonary function testing in patients with lung cancer and found that the FEV1 decline at 4 days postoperatively was more notable in patients with pneumonia than in patients without pneumonia (43.2% VS 32,2%) (11). Hence, regular postoperative pulmonary function testing, combined with other diagnostic assessments such as laboratory testing, radiology, and breathing frequency, could help detect pneumonia.…”
Section: Postoperative Pulmonary Function Testingmentioning
confidence: 99%